The Economic Role of Jews in the Hejaz and Its Influence on Social and Economic Transformations Before Islam - Abu Amsha, Haifa Thabet; Al-Hunaiti, Hanna Mohammed (Journal of Islamic and Religious Studies, 2024)
This research examines the significant economic role played by the Jews in the Hejaz region before Islam and their influence on the social and economic transformations during that period. By exploiting their strategic geographical location and their skills in trade and various crafts, the Jews were able to establish a strong economic network that enhanced their social and economic influence in the region. The research focuses on analyzing the economic activities practiced by the Jews, including agriculture, trade, and industry, with a particular emphasis on usury as a primary tool for accumulating wealth and exercising economic control. Additionally, the study explores the impact of these activities on Hejazi society, including the deepening of social class divisions and the increase in social tensions. Furthermore, the research discusses how the forts built by the Jews in the Hejaz were not merely defensive structures but also significant economic centers that helped them protect their wealth and organize their trade. Lastly, the study offers recommendations for further understanding the economic role of the Jews in the Hejaz and examining the impact of subsequent Islamic policies on economic activities in the region. This research provides a comprehensive and integrated view of the role of Jews in the Hejaz economy before Islam. It aims to enrich the historical understanding of this critical period by analyzing the existing economic and social relationships.